Design And Fabrication Manual Robot Specifically For Robocon 2005 Contest - Amirnudin, Saiful Nizal (Universiti Sains Malaysia, 2005)
This project is about design and fabrication of a manual robot tailor-made for Robocon 2005 competition. Robotics competitions have become common events nowadays. It is main purposes are to generate interests among society and discover talent in robotics field The maximum size and weight allowed are 1000mm length, 1000mm wide, 1500mm high and 10 kg weight. The dangerous energy source can’t be use to build the robot. The electric sources allowed are 24 volt direct current. The Manual robot has to be operated via remote control using a cable connected to it or remote control using infrared rays, only one operator can control manual robot. To design this manual robot theme and rule is used as datum in designing process. Structure sketching and detail drawing had made before the robot has been build. All components used to build the robot must be assembled on the robot. The programming processes are carried out after the structure construction had completed. BASIC Stamp microcontroller will be used as robot controller to program it specific task. The testing method such as straight motion testing, turning testing, and collecting fuel ball testing and release fuel ball testing had been made to archive theme and rule Robocon 2005.